1993
DOI: 10.1002/jrs.1250240812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the deformation of aramid fibres and composites using Raman spectroscopy

Abstract: It is demonstrated that Raman spectroscopy can be used to study both the deformation micromechanics of highperformance aramid polymer fibres and of these fibres in model, single-fibre epoxy resin matrix composites. It is shown that the peak position of the 1610 cm-' aramid Raman band shifts to lower frequency under the action of tensile stress or strain due to the macroscopic deformation leading to direct stretching of the polymer molecules. These strain-induced band shifts can be used to map the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…It has been found that the rate of band shift per unit strain can be associated with the Young modulus of carbon fibres [89,90] and other high-performance fibres [89,91]. In a similar way it has been shown that the deformation of graphene leads to lattice distortion and bond stretching, which ultimately affect its properties [45,90,[92][93][94][95].…”
Section: Mechanical Propertiesmentioning
confidence: 90%
“…It has been found that the rate of band shift per unit strain can be associated with the Young modulus of carbon fibres [89,90] and other high-performance fibres [89,91]. In a similar way it has been shown that the deformation of graphene leads to lattice distortion and bond stretching, which ultimately affect its properties [45,90,[92][93][94][95].…”
Section: Mechanical Propertiesmentioning
confidence: 90%
“…Thus in a system with a high interfacial shear strength, fibre fracture will be more likely then for a system with low interfacial shear strength. The maximum recorded value of interfacial shear strength for the systems studied here, 43 MPa, is close to the shear yield stress of the matrix [8] and could represent interfacial failure by either matrix yielding or fibre/matrix debonding. 6…”
Section: Effect Of Interfacial Shear Strengthmentioning
confidence: 54%
“…For many high-performance fibres the peak positions of certain Raman bands have been demonstrated to shift to lower wavenumber by the application of tensile stress [5][6][7][8][9]. For all the fibres used in this study there is an approximately linear shift of the peak wavenumber, , with axial fibre strain, e f .…”
Section: Single Fibre Deformation In Airmentioning
confidence: 68%
See 2 more Smart Citations